Peran Interlibrary Loan (ILL) sebagai Resolusi Konflik Negosiasi dalam Layanan Informasi: Sebuah Systematic Literature Review - Usnah, Yulianah; Masruri, Anis (Literatify: Trends in Library Developments, 2026)
This study aims to analyze the strategic role of Interlibrary Loans (ILL) as a conflict resolution mechanism through negotiation within the library information services ecosystem. This study fills a gap in the literature that has focused on the technical-operational aspects of ILL, by offering a new perspective emphasizing the social and managerial dimensions of conflict in interlibrary collaboration. The method used was a qualitative systematic literature review (SLR) of published literature from 2021–2025 from the Scopus database. The research design followed PRISMA guidelines with a Boolean strategy, strict inclusion-exclusion criteria, and quality assessment using the CRAAP Test, resulting in 12 selected articles based on currency, relevance, authority, accuracy, and purpose. Data analysis was conducted using thematic analysis using NVivo 12 through a systematic coding process to identify patterns and relationships between the literature. The results identified four main categories of conflict in ILL: operational, technical, financial, and legal. Various strategic resolutions such as integrative negotiation, mediation, standardization of procedures, and the application of technology play a crucial role in managing these conflicts. ILL success is measured through service utilization, user satisfaction, cost efficiency, collaboration intentions, and competitiveness. Theoretically, these findings broaden the conceptualization of ILL beyond just a technical support service to a dynamic and adaptive negotiation platform. Practically, this research provides a structured framework for library managers to develop systematic conflict resolution strategies and reinforces the importance of negotiation competencies and collaborative policies in fostering interlibrary cooperation.